HAS 1: A natural product from soil-isolated Streptomyces species with potent activity against cutaneous leishmaniasis caused by Leishmania tropica - Awada, Bassel; Hamie, Maguy; El Hajj, Rana; Derbaj, Ghada; Najm, Rania; Makhoul, Perla; Ali, Dima Hajj; Abou Fayad, Antoine G.; El Hajj, Hiba (Frontiers in Pharmacology, 2022)
Cutaneous Leishmaniasis (CL) is a neglected tropical disease, classified by the World Health Organization (WHO) as one of the most unrestrained diseases. The Syrian war and the significant displacement of refugees aggravated the spread of this ailment into several neighboring countries in the Eastern Mediterranean Region (EMR). In Syria, Leishmania tropica is identified as one of the most aggressive and endemic identified species, causing localized or generalized lesions, often chronic or relapsing. Pentavalent antimonial drugs are currently used as first line treatment against CL. Nonetheless, these drugs exhibit several limitations, including the repetitive painful injections, high cost, poor availability, and mainly systemic toxicity. Besides, the emergence of acquired parasitic resistance hinders their potency, stressing the need for new therapies to combat CL. Natural products (NPs) epitomize a valuable source in drug discovery. NPs are secondary metabolites (SMs) produced by plants, sponges, or a wide variety of organisms, including environmental microorganisms. The EMR is characterized by its immense biodiversity, yet it remains a relatively untapped area in drug discovery. NPs of the region were explored over the last two decades, but their discoveries lack biogeographical diversity and are limited to the Red Sea. Here, we isolated previously uncultured environmental soil-dwelling Streptomyces sp. HAS1, from Hasbaya region in southeast Lebanon. When fermented in one of our production media named INA, HAS1 produced a crude extract with significant potency against a clinical Leishmania tropica isolate. Using bio-guided fractionation, the bioactive compound was purified and the structure was elucidated by NMR and LC-HRMS. Our findings establish NPs as strong candidates for treating Leishmania tropica and further dwells on the importance of these natural sources to combat microbial infections